Library of Russian Artists in Rome - V.A. Voropaev (Язык и текст)
The article highlights the history of the library of Russian artists in Rome, which N.V. Gogol took part in the creation. The fate of the Roman library of the writer remains unknown to this day. Gogol's books (which belonged to him or those that he could hold in his hands during his stay in Italy), apparently, may be in the private library of A.A. Ivanov in Rome, now owned by relatives of the artist; or in the collections of the Central Scientific Library in Rome, which received the former library of Russian artists — Roman boarders.